Ecological perspectives on variable retention forestry - Martínez Pastur, Guillermo José (2020)
Forest management globally affects the ecosystem services, especially those related to ecosystem functioning and biodiversity conservation, by altering forest structure and composition. The degree of alteration was related to the intensity and type of harvesting; therefore, the major silvicultural challenge is to develop alternatives to mitigate climate change and maintain forest functions and biodiversity while also providing acceptable levels of timber production. Variable retention forestry (VRF) is a highly flexible concept, with continuity of forest cover, structure, function, and species composition, thereby supporting multiple economic, environmental, and cultural goals. This special issue provides an overview of the concepts and applications related to VRF implementation around the world. It shows that VRF has been applied globally for several decades, with varying levels and retention types, depending on local conditions and the economic importance of forestry. The challenges of VRF seem to differ to some extent on different continents, yet the general aims have been accepted in most of the continents. VRF has been successful in mitigating many effects of intensive harvesting, though in some forests of the world, the retention levels are too low to maintain acceptable levels of biodiversity and ecosystem functions. We conclude that an active collaboration between scientists and forest practitioners is needed to realize all of the opportunities provided by VRF in solving global forestry-related issues.